Expressão recombinante de endo-beta-1,4 xilanase identificada no meta-transcriptoma de cupins da espécie Heterotermes tenuis para produção de bioetanol - Alcobaça, Olinda Soares Athaide (2022)
The search for alternative energy sources to the consumption of petroleum and the attention to the environment has awakened the use of new bases in biofuels. In line with this is second-generation ethanol (E2G), which can be produced from lignocellulosic biomass, mainly derived from agricultural residues. For this material to be converted, it needs to undergo hydrolysis of each component. This is one of the stages in which they are most studying, as it is in this stage, the lignocellulosic material is converted into fermentable sugars. Despite being efficient, the use of enzymatic complexes faces the entire production process. In this way, bioprospecting for new lignocellulolytic enzymes is essential because it would bring alternatives for the bioetanol production process, increasing its logistical and economic viability. Xylanases are hemicellulases that degrade xylan, the main component of hemicellulose, formed mainly by pentoses. This enzyme can be applied to several industries, such as paper bleaching, beverage clarification, and bioethanol production. In the latter, xylanases optimize the action of the cellulolytic complex and consequently the yield of bioethanol production. In this study, we prospected an endo-beta-1,4-xylanase (HtpXyl) from the metatranscriptome of termites of the species Heterotermes tenuis, a termite species that is considered a pest of sugarcane. The characterization indicated the presence of two structural sites for catalytic activity. Thus, HtpXyl was cloned into the pET28a vector and pPICZαA for expression in Escherichia coli and Pichia pastoris, respectively. A recombinant protein showed approximately 20kDa, as both systems showed xylanolytic x while tested at 0% activity on 1% Congo red-stained agar, 2%. HtpXyl degraded the substrate on agar both at 30°C and 40°C. These results for collaborative studies to produce an Htp as a biochemical candidate more in-depth for industrial processes of degradation of xylan, among them, of bioethanol.